2020
DOI: 10.1016/j.ijscr.2020.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal arteriovenous malformation treated by laparoscopic surgery using intravenous injection of ICG: Case report with literature review

Abstract: Highlights We report a rare case of small intestinal AVM. Distinguishing small intestinal AVM is difficult. Intravenous injection of ICG made the location and boundary more clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Previous reports showed that ICG FI contributed to reducing the risk of postoperative anastomotic leakage, and that ICG injection into the submucosal layer enables intraoperative visualization of lymphatic flow and can be used for intraoperative navigation in colorectal cancer surgery [5] , [12] , [13] . We performed a PubMed search using keywords such as “ICG” and “arteriovenous malformations”, and found that this is the first reported case of an AVM in the colorectal region that was resected under ICG FI, although some previous reports have shown the utility of ICG FI for AVMs in the small intestinal region [14] , [15] , [16] . In our case, the distribution of abnormal blood vessels caused by the AVM was consistent with the thickened mesentery, weak ICG fluorescence of the intestinal tract and mesentery in this region was suggestive of ischemic enteritis, and the areas of enhanced ICG fluorescence were due to angiogenesis around the region.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that ICG FI contributed to reducing the risk of postoperative anastomotic leakage, and that ICG injection into the submucosal layer enables intraoperative visualization of lymphatic flow and can be used for intraoperative navigation in colorectal cancer surgery [5] , [12] , [13] . We performed a PubMed search using keywords such as “ICG” and “arteriovenous malformations”, and found that this is the first reported case of an AVM in the colorectal region that was resected under ICG FI, although some previous reports have shown the utility of ICG FI for AVMs in the small intestinal region [14] , [15] , [16] . In our case, the distribution of abnormal blood vessels caused by the AVM was consistent with the thickened mesentery, weak ICG fluorescence of the intestinal tract and mesentery in this region was suggestive of ischemic enteritis, and the areas of enhanced ICG fluorescence were due to angiogenesis around the region.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal bleeding accounts for approximately 5% of all GI bleeding cases and is rarely caused by an AVM [ 4 ]. Most small intestinal AVMs occur during adulthood and are very rare in early childhood [ 4 , 5 ]. Etiologically, AVMs are mostly congenital [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…To consider small intestinal AVM, we planned to review the literature. The number of case reports of small intestinal AVM published in English, which had detailed information, was small [ 4 ]. We decided that it would be better to evaluate many cases to comprehensively understand the etiology, pathogenesis, and treatment of small intestinal AVMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arteriovenous malformations are an important subtype of these vascular malformations that rarely occur in the ileum with difficulty to diagnose. 2 Endoscopy, colonoscopy, and computed tomography (CT)-Angiogram can be inconclusive, and patient often needs enteroscopy or capsule endoscopy to localize the site of the lesion. 3 Treatment options depend on size, site, and status of the lesion (actively bleeding or covered by a clot).…”
Section: Introductionmentioning
confidence: 99%